(untitled) (BIRDEM Medical Journal, 2019)
Crohn’s disease (CD) is a disorder of uncertain etiology that is characterized by transmural inflammation of the gastrointestinal tract. CD may involve the entire gastrointestinal tract from mouth to the perianal area. Isolated jejunal involvement of CD is a rare entity. We describe a case of CD involving only jejunum with successful treatment in a 74-years-man who presented with melaena, abdominal pain and significant weight loss. Endoscopy of upper gastro-intestinal tract revealed gastritis and colonoscopy showed small sessile polyp at rectum and sigmoid colon, polypectomy was done accordingly. After few days of polypectomy, he again noticed melaena along with abdominal discomfort and weakness with loss of 4 kg weight within this periods. Diagnosis was confirmed by capsule endoscopy and serology. Treatment was thereafter started with oral steroid and mesalamine sachet. The patient is now on remission and is on regular follow up. CD has propensity to involve the distal small intestine and proximal large bowel. Affected persons usually experience diarrhea and abdominal pain, frequently accompanied by weight loss. Proximal small bowel involvement is less common than distal small bowel or colonic involvement in CD. CD involving proximal small intestine should be suspected in Asian patients with middle gastro-intestinal bleeding. It is associated with a high risk of clinical relapse and morbidity, including the need for abdominal surgery. Different modalities of baseline evaluation and more sophisticated diagnostic modalities may be required for patients with CD involving proximal small bowel. Capsule endoscopy (CE) currently plays an important role in CD. Birdem Med J 2020; 10(1): 68-72